Review. Tron Petit, Jean Claude, What is Open Justice? National Priority. Mexico, National Autonomous University of Mexico, Institute of Legal Research, 2024. - Pérez Sifuentes, Christian Miranda (Revista Internacional & Comparada de Derechos Humanos, 2025)
The book What is Open Justice? National Priority, by Jean Claude Tron Petit, published in 2024 by the National Autonomous University of Mexico (UNAM) through its Institute of Legal Research, stands as a fundamental work in the contemporary study of law in Mexico. At a crucial moment in the history of the administration of justice in the country, the author presents an exhaustive analysis of the concept of open justice and its implementation in the Mexican judicial system, a traditionally opaque field, far removed from active citizen participation. This work is part of the Enclave Jurídica series, a collection that seeks to address central issues of legal practice and offer innovative solutions to the problems currently faced by the judicial field.